Intelligence as a Factor of Efficient Cross-Cultural Interaction - Zasiekina, Larysa V. (Psychological Prospects Journal, 2017)
The results of theoretical and empirical study of cultural intelligence of youth in transboarder regions of Ukraine and Poland are highlighted in the article. The definition of cultural intelligence is suggested as individual ability to interact efficiently in poly-cultural environment. The modern models of cultural intelligence and social-cultural level of individual intelligence in the author’s model are compared.The results of the empirical study of metacognitive, cognitive, motivational and behavioral components show the correlation between indices of bilingualism, professional training in foreign languages departments, living in the transboarder regions of Ukraine and different components of cultural intelligence. The comparative analysis of the different components of cultural intelligence shows that the representatives of transboarder regions have higher indices in the motivational and metacognitive components and represent the higher awareness of necessity to develop cultural intelligence. However there are no differences between subjects in real cross-cultural interaction, expressed in the similar level of behavioral component of cultural intelligence. There are also no differences between the indices of cultural intelligence and frequency of the trips abroad. The necessity of cultural intelligence in micro (family, clinical settings), meso- (international organizations) and macro settings (geopolitical interaction) are described and primary ways of cultural intelligence development of youth in transboarder regions of Ukraine and Poland are outlined. Key words: cultural intelligence, social-cultural level of individual intelligence, archetypical, national-cultural, metacognitive, cognitive, motivational and behavioral components of intelligence.